Malakoplakia of the prostate diagnosed in patients with benign prostatic hyperplasia and elevated prostate-specific antigen - Fredy Leonardo Muñoz Gonzalez (Revista da Faculdade de Ciências Médicas de Sorocaba, 2018)
Malakoplakia is a rare chronic inflammatory disease which affects the genitourinary system, particularly the bladder, the kidneys and the ureters. Isolated involvement of the prostate is much rarer. Differential diagnosis of adenocarcinoma of the prostate can be extremely difficult, because of clinical and imaging similarities. Patients with frequent occurrence of benign prostatic hyperplasia and urinary tract infection need to be prepared for a diagnosis of malakoplakia.